IDENTIFIKASI DAN ANALISIS INTANGIBLE VALUE ATAS BAGI HASIL TABUNGAN DI PERBANKAN SYARIAH (Studi Kasus Penabung di PT Bank Pembiayaan Rakyat Syariah Muamalat Harkat Bengkulu) - Amir Mukadar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Amir Mukadar ; This Research is descriptive, explorative, and implementative, which it’s designed by qualitative and quantitative method. It also uses primary data - which consists of survey, field observation, and interviews - and secondary data – which consists of previous variable that has been issued before. Its variable is explanatory research with some part of it is descriptive qualitative.Another part of it is using qualitative calculation and implementative which empirically analysis and hypotesis in the field. This research showed that identification and intangible value analysis of profit sharing of the saving in PT. BPRS Muamalat Harkat Bengkulu has significant influence toward customer interest in element of kesesuaian aqidah, while in element of kemanfaatan sosial has same effect but with lower value. Ther author expected all things – BPRS managemet, Financial Authority, Moslem Clerc Council – to be better and have maximum effort for socializing sharia banking. It is expected that people have their interest to open their account in sharia bank, especially in PT. BPR Muamalat Harkat. Keywords : Tahwidi String Relation (TRSR) Tabungan, Intangible Value for profit sharing